DISCLOSURE OF BANK MUAMALAT’S CAPITAL ADEQUACY TO SUPPORT SUSTAINABILITY AND STRENGTHENING THE BANKING SYSTEM IN INDONESIA - Mahardiyanto, Agus; Prajasari, Anniza Citra (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
This research aims to determine and analyze the capital adequacy of Bank Muamalat and reveal the adequacy of existing capital for the sustainability and strengthening of the banking system in Indonesia in the future. This research employs a qualitative methodology with a descriptive orientation. The data source in this research uses secondary data obtained from texts, manuscripts, online newspapers and documents, which in this research are the monthly financial reports of the Bank Muamalat company for the 2017-2022 period. The data analysis technique used is a triangulation (combined) technique. The results of this research are that disclosure of capital adequacy has a positive impact on encouraging sustainability and strengthening the existing banking system in Indonesia. Because this will help investors, potential investors and the public to entrust their funds to be managed by Bank Muamalat.